Culture of the Recreation, Democracy and Political Conscience - Reyes, Alixon (2014)
Recreation is a universal cultural and intangible patrimony. Besides, it has to do with all those experiences lived and felt by a human being while a transformation takes place towards it that he wishes, needs and gasps. But, the recreation has been confused with entertainment and amusement, elements that form a way of being and a way of thinking producing a cultural emptying of the recreation turning it into a banal and instrumental matter. And do not think that this is neutral and innocent. On the contrary, it is a trend that marks the fingerprint of a neocoloniality. This way, the recreation is done, is bought and sold, is programmed and is planned, offers to the measurement the one who can buy it and the one who can pay it, leaving of side the experience humanizes as vital point.